SUBIKA ART: AN EARLY VISUAL ART FORM OF MANIPUR - Sapha Wangam Apanthoi M, Yumnam (ShodhKosh: Journal of Visual and Performing Arts, 2022)
There are six surviving manuscripts under the category of Subika namely Subika, Subika Achouba, Subika Laishaba, Subika Choudit, Subika Cheithil, and Thengrakhel Subika. For this paper the manuscript “Subika Laishaba’’ has been discussed. Illustration of Subika Laishaba is the manuscript painting among the earliest surviving visual arts forms of Manipur. Though the advent of Subika Laishaba paintings has lately acquired from various individual collections, the painting possesses an interesting area of studying its visual elements and cultural values of Meitei community. The painting of Subika Laisaba is a composition of cultural motifs made by pre-existing features and other influences stimulated from their cultural worldviews. Such cultural ethics of scriber makes them to create a unique style seen as indication of establishing a thought of school in which cultural and regional features are highlighted. Subika Laishaba manuscripts represent the direct and authentic continuation of the tradition of Meitei cultural life projected through visual images. Though there is no particular founder mentioned in the royal chronicle/history known as Cheitharol Kumbaba, there may be a possibility that the art form may have existed when the writing tradition was introduced in the state. This paper is an attempt to study its purposes and visual language portrayed in the Subika Laishaba manuscripts to understand its school in the realm of visual art. This study of visual language may be able to work without judgment and self-criticism.